DID BOYS REALLY TELL JOKES IN ANCIENT PHAESTUS? - Anna J. Strataridaki (Journal of Ancient History and Archaeology)
In a preserved fragment, the historian Sosicrates records a custom which was practiced among the ancient Phaestians in Crete: the boys were trained to tell witty jests from early childhood. The author of this paper proposes the educational purpose of the custom for the boys’ future military and social role. The practice is interpreted as a pedagogical measure aimed to control the untamed nature of the young trainees, and to cultivate their cohesiveness as a group. The custom seems to have taken place at the syssitia, where, according to ancient sources, Cretan agōgē was realized. The Phaestian jesting is also examined as a probable precursor for wits spoken in Crete today.